2019
DOI: 10.1186/s42480-019-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-phase hydrogenation of bio-refined succinic acid to 1,4-butanediol using bimetallic catalysts

Abstract: Development of a Crotalaria juncea based biorefinery produce large quantity of waste glycerol after trans-esterification of the juncea seeds. This glycerol, after purification, is used as a substrate for producing succinic acid on a microbial route. Hydrogenation of this bio-refined succinic acid is carried out under high pressure in order to produce 1,4butanediol (BDO) using a batch slurry reactor with cobalt supported ruthenium bimetallic catalysts, synthesized inhouse. It is demonstrated that, using small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The monomers can either be derived from petrochemical or bio-based chemicals (bacterial fermentation) [ 21 ] Basically, PBS is synthesised through a polycondensation reaction between 1,4-butanediol and succinic acid [ 22 ]. For bio-based monomers, succinic acid could be derived from glucose, which can be obtained from various sources of bio-feedstock through bacterial fermentation [ 23 ], while hydrogenation of succinic acid will produce 1,4-butandiol, which is required for PBS synthesis [ 24 ]. The synthesis of PBS requires two steps, which are esterification between diacid (succinic acid) and diol (1,4-butanediol), forming oligomers, followed by polycondensation at high temperature to form high MW PBS [ 21 , 22 ].…”
Section: Bioplasticsmentioning
confidence: 99%
“…The monomers can either be derived from petrochemical or bio-based chemicals (bacterial fermentation) [ 21 ] Basically, PBS is synthesised through a polycondensation reaction between 1,4-butanediol and succinic acid [ 22 ]. For bio-based monomers, succinic acid could be derived from glucose, which can be obtained from various sources of bio-feedstock through bacterial fermentation [ 23 ], while hydrogenation of succinic acid will produce 1,4-butandiol, which is required for PBS synthesis [ 24 ]. The synthesis of PBS requires two steps, which are esterification between diacid (succinic acid) and diol (1,4-butanediol), forming oligomers, followed by polycondensation at high temperature to form high MW PBS [ 21 , 22 ].…”
Section: Bioplasticsmentioning
confidence: 99%
“…Succinic acid is employed in various applications as an essential C-4 building block or precursor for numerous critical speciality chemicals, including tetrahydrofuran, adipic acid, N-methyl pyrrolidinone, 2-pyrrolidinone, gamma-butyrolactone, succinamide, putrescine, succinonitrile, and succinate salts [37]. The acid is also a precursor for 1,4-butanediol production through hydrogenation and reduction [38].…”
Section: Succinic Acid and Its Associated Bioplasticsmentioning
confidence: 99%
“…Ruthenium-containing catalysts have been successfully employed due to their ability to completely hydrogenate carboxylic acids into alcohols. 112,113 Baidya et al reported cost effective production of BDO from a biorefinery, where waste glycerol generated from biodiesel production was fermented to give SA, which was subsequently hydrogenated into BDO. 113 Bio-based BDO had a global market of $191 million in 2020, 114 compared to $9.7 billion total BDO market.…”
Section: Class C Bio-based Polymersmentioning
confidence: 99%